2014
DOI: 10.1245/s10434-014-4098-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction and Revision Surgery for Implant-associated Breast Deformities Using Porcine Acellular Dermal Matrix: A Multicenter Study of 156 Cases

Abstract: Complication rates using porcine acellular dermal matrix in breast reconstruction are comparable to complication rates reported in studies using human acellular dermal matrices. Thus, porcine acellular dermal matrices can safely be applied in breast reconstructive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 37 publications
1
27
1
1
Order By: Relevance
“…After passing through the selection process, 20 studies fit the criteria and were analyzed (Fig. ) . Only one prospective study was found, and the others were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After passing through the selection process, 20 studies fit the criteria and were analyzed (Fig. ) . Only one prospective study was found, and the others were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies representing 1,126 cases reported the results following nipple‐sparing mastectomy and the others did not specify the types of mastectomy. Twelve studies reported on two‐stage prosthetic reconstruction using a tissue expander, one regarding one‐stage direct‐to‐implant, and five using both methods. Four studies used ADM in all cases, six did not use it at all, and four used it selectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall capsular contracture rate in our retrospective study was 6%, including one patient with a history of chemotherapy and one patient with a history of radiotherapy. Within the current literature, capsular contracture rates after ADM implantation differ from 0 up to 3.75% [6, 1119]. …”
Section: Discussionmentioning
confidence: 99%